GOVERNING MANGROVE TOURISM VILLAGES FOR SUSTAINABLE ECONOMIC OUTCOMES: INSIGHTS FROM A SYSTEMATIC LITERATURE REVIEW - Tri Achmad Budi Susilo; Syakur, Abd.; M Khusni Mubarok; Moch. Dicky Riza; Sunardi (EDUCATUM: Scientific Journal of Education, 2025)
Tourism villages represent a strategic solution for generating employment and promoting sustainable economic development in rural areas, particularly in the context of the Society 5.0 era. To ensure the sustainability of tourism village development, regional management must prioritize environmentally sound and cost-effective principles supported by educational approaches that strengthen community knowledge, skills, and environmental awareness. One proposed strategy is the application of the ecovillage concept, especially in coastal village development through the conservation-based utilization of mangrove resources. This study aims to identify policy models that support the management of sustainable mangrove tourism villages by integrating education for sustainable development as a core component of community empowerment. The research employed a Systematic Literature Review, with literature searches conducted across several academic databases and article selection following the PRISMA protocol. The findings indicate that the current condition of tourism villages has not yet achieved the expected level of sustainability, largely due to local government policy models that insufficiently support educational programs, capacity building, and community learning processes related to sustainable mangrove management in Malang Regency. Priority analysis using SWOT Analysis and the Analytical Hierarchy Process (AHP) reveals that sustainable policy development should emphasize environmental education, participatory learning, and continuous training for local communities to minimize conflicts of interest and maximize socio-economic benefits. Overall, the study highlights that the integration of education-based policy interventions in mangrove tourism village management is essential for strengthening community competence, fostering environmental stewardship, and improving local welfare through sustainable mangrove ecotourism